Calculation Method for Bearing Capacity of Bottom-Supported Anti-Pull Piles in Layered Foundation - Jianming Zeng; Zhengzhen Wang; Xuwei Chen; Na Lian; Feng Li (Advances in Civil Engineering)
In recent years, with the rapid development of cities, the utilization rate of underground space has gradually increased, and anti-pull piles have also been widely used in practical engineering. In this paper, the failure surface form of the anti-pull pile was assumed, the soil parameters of each soil layer in the layered foundation and the Poisson effect generated by the anti-pull pile under the action of the uplift force was considered, and the calculation formula for the bearing capacity of the anti-pull long pile in the layered foundation was obtained, which was verified by on-site test data. Finally, the parameter range of the calculation method was analyzed. The results show that when the aspect ratio of the anti-pull pile is large, and the elastic modulus of the anti-pull pile is small, the Poisson effect of the anti-pull pile is obvious, and the increment of pile side friction caused by the Poisson effect is also large. When the value range of parameter N is 50 ≤ N ≤ 100, the calculation results are more reasonable. The average error of the lower limit N = 50 is 11.7%, and the average error of the upper limit N = 100 is 5.3%.